Sales Promotion and Growth of Bread Bakery Business in Kabale Municipality: A Case Study of Elite Bakery. - Ahurira, Isabel (Kabale University., 2024)
The study research focused on the findings of sales promotion and sales volume of bread in Elite bakery. A case study of Uganda Elite bakery, Kabale municipality. The objectives of the study were to find out how sales promotion affects sales of bread in Elite Bakery, to find out sales promotion activities used by Elite Bakery in Kabale Municipality to establish the relationship between sales promotion and sales volume of bread in Elite Bakery in Kabale Municipality. In chapter two, there was a critical review of the issues that have been explored and studied both theoretically and empirically in the existing literature on sales promotion as an independent variable and sales volume as the dependent variable. In chapter three this is where the methods of data collection were put into action. The research used both qualitative and quantitative methods of data collection and analysis. The research used simple random sampling techniques in collecting and analyzing data and was used to provide equal chances to the sample size. Purposive sampling was also used to collect data from respondents who participated in the study. Chapter four showed the findings of the study obtained from the field interpreting the results and analyzing them based on the specific objectives of the study and chapter five portrayed the summary of findings, conclusion, and recommendations on sales promotion and sales volume of bread in Elite bakery. A case study of Uganda Elite bakery, Kabale district.